2022
DOI: 10.3390/su142215256
|View full text |Cite
|
Sign up to set email alerts
|

Productive and Sustainable H2 Production from Waste Aluminum Using Copper Oxides-Based Graphene Nanocatalysts: A Techno-Economic Analysis

Abstract: Hydrogen has universally been considered a reliable source of future clean energy. Its energy conversion, processing, transportation, and storage are techno-economically promising for sustainable energy. This study attempts to maximize the production of H2 energy using nanocatalysts from waste aluminum chips, an abundant metal that is considered a potential storage tank of H2 energy with high energy density. The present study indicates that the use of waste aluminum chips in the production of H2 gas will be fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Other feasible methods are mainly focused on the modification of aluminum composition and structure. That can be done via its melting together with various metals (e.g., Fe, Sn, Cu, Li, Ga, In, Sn) [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] or ball milling with salts (e.g., NaCl, KCl, NiCl 2 , CoCl 2 ) [ 52 , 53 , 54 , 55 , 56 ], oxides and hydroxides (Bi(OH) 3 , AlOOH, Al(OH) 3 , Al 2 O 3 , TiO 2 , Co 3 O 4 , Cr 2 O 3 , MoO 3 , Bi 2 O 3 , CuO, Cu 2 O) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ], and metals (Cu, Bi, Sn, Pb, Fe, Ni, Zn, Ga, In) [ 56 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Experiments with aluminum granules and distilled water under 200–280 °C proved that aluminum vulnerability to oxidation was critically dependent on the amount of impurities in aluminum alloys and their nature [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other feasible methods are mainly focused on the modification of aluminum composition and structure. That can be done via its melting together with various metals (e.g., Fe, Sn, Cu, Li, Ga, In, Sn) [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ] or ball milling with salts (e.g., NaCl, KCl, NiCl 2 , CoCl 2 ) [ 52 , 53 , 54 , 55 , 56 ], oxides and hydroxides (Bi(OH) 3 , AlOOH, Al(OH) 3 , Al 2 O 3 , TiO 2 , Co 3 O 4 , Cr 2 O 3 , MoO 3 , Bi 2 O 3 , CuO, Cu 2 O) [ 57 , 58 , 59 , 60 , 61 , 62 , 63 ], and metals (Cu, Bi, Sn, Pb, Fe, Ni, Zn, Ga, In) [ 56 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Experiments with aluminum granules and distilled water under 200–280 °C proved that aluminum vulnerability to oxidation was critically dependent on the amount of impurities in aluminum alloys and their nature [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the use of chemical additives for addressing this issue, including the use of alkalis [6][7][8][9][10] or salts [11] in aqueous solutions, as well as the activation of aluminum by various metals, silicon, graphite, chlorides, and oxides [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Xinren Chen et al have demonstrated a unique aluminum corrosion mechanism, which could have promising implications for its use in energy production [27].…”
Section: Introductionmentioning
confidence: 99%